2009
DOI: 10.1007/s10734-009-9290-1
|View full text |Cite
|
Sign up to set email alerts
|

University drop-out: an Italian experience

Abstract: University students' drop-out is a crucial issue for the universities' efficiency evaluation and funding. In this paper, we analyze the drop-out rate of the Economics and Business faculty of Sapienza University of Rome. We use administrative data on 9,725 undergraduates students enrolled in three-years bachelor programs from 2001 to 2007 and perform a Generalized Linear Mixed Model. Our aim is to improve the general understanding of the students' withdrawing focusing on personal characteristics of students rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 16 publications
6
74
1
6
Order By: Relevance
“…The score effect on course change is mixed: a higher score increases the risk of change in social sciences but decreases those in scientific studies, and no effects are found among students in professional health studies and humanities. As suggested by Belloc, Maruotti, and Petrella (2010), this mixed evidence may be due to the fact that individuals with high educational backgrounds are more sensitive to courses and, when they realize they are not enjoying them, they change. Students entering university with a polytechnics diploma and particularly those with a vocational education are more prone to withdraw (an exception is observed in professional health studies among students from polytechnics) and are less likely to obtain degrees (although the effect is only weakly significant among students in professional health studies) than students from high schools.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The score effect on course change is mixed: a higher score increases the risk of change in social sciences but decreases those in scientific studies, and no effects are found among students in professional health studies and humanities. As suggested by Belloc, Maruotti, and Petrella (2010), this mixed evidence may be due to the fact that individuals with high educational backgrounds are more sensitive to courses and, when they realize they are not enjoying them, they change. Students entering university with a polytechnics diploma and particularly those with a vocational education are more prone to withdraw (an exception is observed in professional health studies among students from polytechnics) and are less likely to obtain degrees (although the effect is only weakly significant among students in professional health studies) than students from high schools.…”
Section: Resultsmentioning
confidence: 99%
“…It is included in the statistical models as a regressor, in the hypothesis that older students are more likely to have interrupted careers than those enrolling immediately after leaving school, in view of time constraints (e.g., jobs, family), higher opportunity costs, and a shorter period of time during which they can benefit from their educational investment (Charlton, Barrow, and Atkinson 2006;Lassibille and Gomez 2009). Findings are not always consistent (Lassibille 2011); another point to be considered is the fact that older students may have stronger motivations to conclude their degree courses once they have enrolled (Belloc, Maruotti, and Petrella 2010).…”
Section: Covariatesmentioning
confidence: 95%
See 2 more Smart Citations
“…Earlier literature finds that the decision to drop out of a university is related to numerous background factors, such as academic preparedness and ability (e.g., Montmarquette, Mahseredjian and Houle, 2001;Arulampalam Naylor and Smith, 2004;Johnes and McNabb, 2004;Belloc, Maruotti and Petrella, 2010); family backgrounds (e.g., Lassibille and Gomez, 2008;Vignoles and Powdthavee, 2009;Gury, 2011;Aina, 2013); regional labour markets (e.g., Di Pietro, 2006) and working while studying or financial aid (e.g., . Nevertheless, existing empirical literature offers little evidence on how individuals succeed after they dropout from a university.…”
Section: Introductionmentioning
confidence: 99%